POLIGAMI DI INDONESIA (SEBUAH ANALISIS NORMATIF-SOSIOLOGIS) - Agus Sunaryo (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
This paper discusses the dynamics of polygamy in Indonesia, both as discourse and in the application form. Polygamy as adiscourse has undergone an extraordinary debate among pros and cons. Meanwhile, polygamy in the application in everyday life haveexperienced abuses the intent of the parties who benefited, namely the male. Therefore, the need for solutions related to polygamy inaccordance with the rule. In this paper, the authors not only discuss again about polygamy in Indonesia, but also has a solution in the form oflaw, both Islamic and universal. The author provides solutions based on normative and sociological analysis that has a humanist andtheological relationships.